The Great Transformation the political and economic origins of our time - Polanyi, Karl. (Boston Beacon Press, 2001)
In this classic work of economic history and social theory, Karl Polanyi analyzes the economic and social changes brought about by the "great transformation" of the Industrial Revolution. His analysis explains not only the deficiencies of the self-regulating market, but the potentially dire social consequences of untempered market capitalism. New introductory material reveals the renewed importance of Polanyi's seminal analysis in an era of globalization and free trade.
Includes index
Keywords: Development